Maintaining sustainable accounting systems in small business - Carvalho, Luísa Cagica 1970-; Truant, Elisa 1982- (IGI Global, Disseminator of Knowledge, 2018)
"This book provides relevant insights for academics, deepening the topic of sustainability accounting systems within small business. It also provides contributions about the features of sustainability accounting systems and, in particular, how the economic, social and environmental aspects are related to each other in the company's management and performance"...
Keywords: Small business -- Accounting